The Colombian Caribbean in images: foreign expeditions around the earthquake in Panama at the end of the 19th century - Gómez Castaño, Leguis Antonio (2021)
Received: 24-01-2021. Approved: 15-03-2021. In 1882 the Panama region suffers one of the most devastating seismic events in its history. Alongside with the construction of the big channel, the earthquake sparked academic and scientific interest of foreigners who traveled to the Colombian Caribbean to pay their visit. As a result of those visits carried out between 1882 and 1886, a photographic archive was produced and this article tries to rescue.